THE IMPLEMENTATION OF INQUIRY-DISCOVERY LEARNING - K Nurdin; Hanafy Sain Muh.; Mustami Halifa Muhammad (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
In teaching learning activity, a method is needed by every teacher. A teacher cannot do his task if he does not master a teaching method which proposed by the experts in education psychology. A teaching method is a way taken by a teacher in delivering the lesson to the students and in involving the active and dynamic interaction between teacher and students so the learning objective can be achieved. Inquiry and discovery method is the way to present the lesson which involves the students in a mental process to discover the knowledge. Inquiry discovery is a mental process in which an individual assimilates concepts and principles to be knowledge. This article exposes the definition, method, basic concept, application, strength and weakness of inquiry-discovery learning.